Comparison of Volatile Compounds of Iranian Black Teas During Process - Zadeh Azin, Nasrollah; Parviz, Azar; Kambiz, Larijani; Haghighat Shiva, Roofigari (Asian Journal of Chemistry, 2010)
Volatile free compounds in fresh, withered, fermented and dried leaves in two samples of Iranian tea were analyzed by gas chromatography and gas chromatography mass spectrometry during black tea manufacture. In sample I, linalool decreased during withering and fermentation and increased in the drying stage but never reached the highest level in fresh leaves and α-farensene decreased during all stages, especially during withering but at the end of drying, the amounts of linalool and farensene were equal. In sample II, linalool decreased sharply during manufacture but it is noticeable that a-farensene increased greatly during all stages, so it can be taken as the main fraction in black tea aroma in this sample. Amount of geraniol is not noticeable in both the samples except in the withering stage.